THE EFFECT OF HEALTH EDUCATION WITH PROACTIVE COGNITIVE GAME TO TEENAGER KNOWLEDGE ABOUT HIGH RISK OF EARLY MATRIMONY - Dedes Fitria; Fuadah Ashri Nurfurqoni (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2020)
Case of early marriage still occur in many parts of the world and become a concern to the international community because of the high risk complications during pregnancy, labour at a young age, that  increasing maternal and infant mortality rates.  Indonesian Demographic and Health Survey in 2012 showed 12.8% of women ages 15-19 were married. The social phenomenon of getting pregnant before getting married is now increasing in Bogor. In 2013 there were 1,626 couples are early matrimony because of pregnancy  with an age range of 16-19 years and 8,130 matrimony which 20 percent matrimony at age 19-20 years. This young couple is still at school age. The average age for males is under 19 years and for females under 16 and 17 years. One of effort that can be done to help teenagers solve these problems is through reproductive health education which is usually called counseling learning methods that are more appropriate  with the discussion method to get conclusion and not be rigid when give counseling. Based on study, the proactive cognitive game method is one of the effective learning methods to increase teenager knowledge in reproductive health education. This study aims is determine the effect of health education with proactive cognitive game methods to knowledge and attitudes of teenagers about the high risk of early matrimony.  Design of this study is Quasi experimental pre-post test design with control group with the intervention using proactive cognitive game method. Sampling technique use purposive sampling. The inclusion criteria in this study were teenagers aged 15-19 years, students of class XI-XII, willing to be respondents. Variables were measured with knowledge and attitude questionnaire. Data analyze using the Mann Whitney test. Data was collected in August 2018. Results in intervention group , there was a change in the mean of knowledge by 4 points, from 24.53 at the pre-test to 28.28. Whereas in the control group the change in value occurred only 1 point from 20.50 to 21.73 at post test value. There is an effect of providing health education through proactive cognitive games to teenager knowledge about the impact of early matrimony with p value  <0.05. Suggestion: it is necessary to increase the use of interactive and interesting methods in providing health education with the target is teenager so that expected results can be achieved efficiently.